Analisa penyebab kerusakan produk cocopeat menggunakan diagram fishbone pada UMKM XYZ - Dwi Adi Prastyo; Ira Arianti; Rois Indriawan; Irfan Cholid; Nurimansyah (Universitas Atma Jaya Yogyakarta, 2026)
[Analysis of the causes of damage to cocopeat products using a fishbone diagram in MSME XYZ] The cocopeat processing industry at the micro, small, and medium enterprise (MSME) level faces serious challenges related to product defects that negatively affect product value and consumer trust. This study aims to identify types of product damage in cocopeat and to systematically analyze the contributing factors at MSME XYZ. A descriptive qualitative approach was employed, guided by a quality management framework centered on root cause analysis. Data were collected through in-depth interviews with the business owner and production operators. The collected data were analyzed using a fishbone diagram with the 5M+1E categorization framework, encompassing the factors of man, machine, material, method, measurement, and environment. Fishbone diagram analysis revealed four primary factors contributing to cocopeat product defects: insufficient operator supervision during the packaging process (man), absence of scheduled maintenance for the shredding machine (machine), low pH characteristics of raw materials due to geographical factors (material), and manual portioning processes without standardized weighing tools (method). Product defects in MSME X's cocopeat are not caused by a single factor but rather by a combination of systemic weaknesses in the production process spanning human resources, equipment, raw materials, and work procedures, thereby necessitating comprehensive and structured improvements.